Tanggung Jawab dan Perlindungan Hukum Terhadap Kreditur dalam Kasus Wanprestasi Utang Piutang - Tasya Djafar (Universitas Proklamasi 45, 2026)
Defaults in debt and credit agreements not only have an impact on the legal relationship between debtors and creditors, but also pose challenges in the implementation of existing legal mechanisms, especially in the context of increasingly complex developments in financial technology. This research aims to comprehensively analyze the enforcement of the debtor's legal responsibility and the implementation of legal protection for creditors in legal practice in Indonesia. The method used is normative juridical with an analytical descriptive approach, through a study of laws and regulations, legal doctrines, and court decisions related to default on debt and credit. Data is obtained from literature studies and analyzed qualitatively to describe the application of legal norms and obstacles in enforcing debtor responsibility and creditor protection, especially through material security and its execution mechanism. The results show that the debtor's responsibility for default is regulated in the Civil Code and enforced through court decisions that require payment of debts and compensation. Creditor protection through mortgage and fiduciary rights provides a strong legal basis, but still faces technical and procedural obstacles. This research emphasizes the importance of improving dispute resolution and updating regulations that are adaptive to the development of financial technology to ensure legal certainty. It is also recommended that further research be conducted using an empirical approach to understand the dynamics of default and creditor protection in various economic sectors.